Diseño de un sistema de control de posición y transporte para bandejas plásticas en una máquina dosificadora de grasa en la empresa ControlSoft - Porras-Villegas, Marco Vinicio (Instituto Tecnológico de Costa Rica, 2014)
This project was done in a dosing machine grease washers in the ControlSoft company, it is located in Coronado, San Jose, this machine should fit the washers greased trays by a manipulator (robotic arm), but it happens that the mechanism placement of the trays they differ in position of a repeat to another, so that the coordinates change and the handler can’t locate the washers, before such issue, a person need for this by adjusting the position of the tray and the corresponds to the coordinates that the handler has set, creating a dependence on an operator in a process for which the machine was designed to work independently. In addition the system has a conveyor belt having inserted the function of serving as a basis for the trays and remove once filled washers, this transport system has vibrations and multiple adjustments so you want to change. To solve the problem silvery what was proposed was a system determined by means of distance measuring sensors, the position of the tray, with each repetition you perform a correction of the coordinates to the manipulator. Together with a base which replaces the start of the conveyor, so that the belt conveyor is designed as not to be inserted into the machine it is to be placed to one side of it.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Electromecánica e Ingeniería en Electrónica, 2014.
Keywords: Banda Transportadora; Coordenadas; Sensor de Medición; Arandelas